2007
DOI: 10.1007/s11135-007-9094-2
|View full text |Cite
|
Sign up to set email alerts
|

When is a Compositional Effect not a Compositional Effect?

Abstract: The question of compositional effects (that is, the effect of collective properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…The effects of variables aggregated at the school level have been described as phantom effects (Harker & Tymms, 2004;Pokropek, 2014;Televantou et al, 2015;Perry, 2019). Hutchison (2007) shows mathematically that spurious effects of aggregated variables occur even in properly specified models and remain as sample sizes approach infinity.…”
Section: Correlation Of School Effects Across Statistical Modelsmentioning
confidence: 99%
“…The effects of variables aggregated at the school level have been described as phantom effects (Harker & Tymms, 2004;Pokropek, 2014;Televantou et al, 2015;Perry, 2019). Hutchison (2007) shows mathematically that spurious effects of aggregated variables occur even in properly specified models and remain as sample sizes approach infinity.…”
Section: Correlation Of School Effects Across Statistical Modelsmentioning
confidence: 99%
“…Although there is strong empirical evidence and a large number of studies to support both the BFLPE (see Marsh & Seaton, 2015 for an overview) and the REM (Marsh & Craven, 2006), results regarding the peer spillover effect, although widely accepted, are inconsistent (Hattie, 2002; Hutchison, 2007; Nash, 2003; Televantou et al, 2015). Moreover, methodological advances show that the presence of such positive compositional effects of achievement might be the result of unreliability at the individual level for which has not been accounted for.…”
mentioning
confidence: 99%
“…As Gorard (2006a) notes, the difficulties of estimating school effects using noisy data are already sizable and these are compounded when studying compositional effects which are a fraction of the overall school effect. There are now several methodological studies that have shown that spurious (or 'phantom') compositional effects can arise from pupil-level measurement error (Harker and Tymms 2004;Hutchison 2007;Pokropek 2014;Televantou et al 2015) or the failure to take pupil-level control variables such as SES into account (Nash 2003).…”
Section: Phantom Compositional Effectsmentioning
confidence: 99%